2006
DOI: 10.1161/circulationaha.105.583351
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Lys27 Instead of Asn27 in Human Phospholamban Promotes Sarcoplasmic Reticulum Ca 2+ -ATPase Superinhibition and Cardiac Remodeling

Abstract: Background-Phospholamban (PLN) is an inhibitor of the Ca 2ϩ affinity of sarcoplasmic reticulum (SR) Ca 2ϩ -ATPase (SERCA2). The amino acid sequence of PLN is highly conserved, and although all species contain asparagine (Asn), human PLN is unique in containing lysine (Lys) at amino acid 27. Methods and Results-Human PLN was introduced in the null background. Expression of human PLN, at similar levels to mouse wild-type PLN, resulted in significant decreases in the affinity of SERCA2 for Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 35 publications
(36 reference statements)
5
32
0
Order By: Relevance
“…It is noteworty that the PLB protein of rat cardiac myocytes is mostly present as a pentameric oligomer (Fig. 6C), in agreement with previous reports demonstrating that the PLB monomer-to-pentamer ratio is much lower in murine than in human heart muscle (35). On the other hand, a small band corresponding to PLB monomer appears in TG-treated myocytes (Fig.…”
Section: Effects Of Cna Subunit Gene Silencing or Nfat Displacement Fsupporting
confidence: 91%
“…It is noteworty that the PLB protein of rat cardiac myocytes is mostly present as a pentameric oligomer (Fig. 6C), in agreement with previous reports demonstrating that the PLB monomer-to-pentamer ratio is much lower in murine than in human heart muscle (35). On the other hand, a small band corresponding to PLB monomer appears in TG-treated myocytes (Fig.…”
Section: Effects Of Cna Subunit Gene Silencing or Nfat Displacement Fsupporting
confidence: 91%
“…This appears to be particularly important in humans, as chronic PLB deficiency owing to genomic mutations was associated with cardiomyopathies. [28][29][30] Whereas in mice complete knockout of PLB (as may also be achieved by RNAi) was able to rescue the severe cardiomyopathic phenotype of MLP knockout mice, 31 suggesting that unregulated PLB silencing is appropriate in this species, application in humans most probably requires regulatable RNAi.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, in a study in which human PLB was expressed in transgenic mice, Kranias and co-workers concluded that lysine at position 27 makes PLB superinhibitory, inducing heart failure and cardiac remodeling in transgenic mice (38,39). Because of these effects observed in mice, novel functions for PLB in human myocardium were proposed (38,39). However, in the present study, we determined that human PLB (with Lys 27 ) inhibits SERCA2a activity to the same extent as canine PLB, which has Asn 27 .…”
Section: Mechanism Of Plb Inhibition In Sr Vesicles-it Is Largelymentioning
confidence: 99%